Design of an iBeacon-based indoor navigation system (back-end system) - Sun, Peng (2017)
With the development of the technology the number of applications for data services and multimedia services increase rapidly. At same time the demand for information service based on navigation becomes higher and higher, especially for BVI people. Compared with the previous WiFi positioning technology, the low power-consumed Bluetooth 4.0 is available to navigate with higher precision, lower power consumption and cost. In the meantime, the iBeacon technology proposed by Apple Inc. It will be an important progress in the commercialization of low power-consumed Bluetooth 4.0. This paper analyses the research status of the current indoor positioning algorithm and programming technologies. The project is that by using low power Bluetooth 4.0 technology, through monitoring the broadcast signal of low power Bluetooth devices arranged in specific location by front-end and interacting with back-end system, the front-end can get the navigation route.